2018
DOI: 10.1098/rsif.2018.0249
|View full text |Cite
|
Sign up to set email alerts
|

Modularity speeds up motor learning by overcoming mechanical bias in musculoskeletal geometry

Abstract: We can easily learn and perform a variety of movements that fundamentally require complex neuromuscular control. Many empirical findings have demonstrated that a wide range of complex muscle activation patterns could be well captured by the combination of a few functional modules, the so-called muscle synergies. Modularity represented by muscle synergies would simplify the control of a redundant neuromuscular system. However, how the reduction of neuromuscular redundancy through a modular controller co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 78 publications
(157 reference statements)
3
19
0
Order By: Relevance
“…After compatible virtual surgeries (like in visuomotor rotations as they can be seen as a type of compatible perturbation), cursor trajectories that can be generated within the know repertoire of motor commands -- by recombining existing muscle synergies -- provide information about the novel mapping between motor commands and task space and the inaccurate cursor trajectories can thereby be used to improve performance in the following trials by calculating the error between the estimated trajectory and the actual trajectory. More specifically, in a synergy-based controller (Hagio and Kouzaki 2018), a compatible virtual surgery can be overcome by using existing muscle synergies and associating new synergy combinations to the movement targets. The hypothesis is that a new mapping of visual targets to synergy coefficients is learned and that such adaptive process occurs faster than the learning of new synergies.…”
Section: Discussionmentioning
confidence: 99%
“…After compatible virtual surgeries (like in visuomotor rotations as they can be seen as a type of compatible perturbation), cursor trajectories that can be generated within the know repertoire of motor commands -- by recombining existing muscle synergies -- provide information about the novel mapping between motor commands and task space and the inaccurate cursor trajectories can thereby be used to improve performance in the following trials by calculating the error between the estimated trajectory and the actual trajectory. More specifically, in a synergy-based controller (Hagio and Kouzaki 2018), a compatible virtual surgery can be overcome by using existing muscle synergies and associating new synergy combinations to the movement targets. The hypothesis is that a new mapping of visual targets to synergy coefficients is learned and that such adaptive process occurs faster than the learning of new synergies.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the experiments by Berger et al [4] that indicate that it is more difficult (i.e., requires more trials and time) to learn movements that are incompatible with existing experimentallydetermined muscle synergies than to learn movements that are consistent with measured synergies. Hagio et al [24] previously showed that modularity speeds up motor adaptation to rotational perturbations in an isometric force production task. We extend their result by studying reaching movements and by studying the effects of modularity on motor learning, not just adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments by Berger et al [5] indicate that it is more difficult (i.e., requires more trials and time) to learn movements that are incompatible with existing experimentally-determined muscle synergies than to learn movements that are consistent with measured synergies. In a computational study, Hagio et al [24] showed that modularity speeds up motor adaptation to rotational perturbations in an isometric force production task. We extend these results by studying reaching movements and by studying the effects of modularity on motor learning, not just adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In a computational study, Hagio et al [24] showed that modularity speeds up motor adaptation to rotational perturbations in an isometric force production task. In Berger et al [5], after a virtual tendon rearrangement surgery, subjects had difficulty adapting to perturbations that were incompatible with synergies identified pre-virtual-surgery, whereas they quickly adapted to perturbations compatible with the synergies.…”
Section: Introductionmentioning
confidence: 99%